The translation of foods and beverages terms in mitch albom's novel the first phone call from heaven into telepon pertama dari surga by Julanda Tantani - Risa Heruwati (Faculty of Adab and Cultural Sciences State Islamic University Sunan Kalijaga, 2016)
st,1/ws.c.1